Ehrlichiosis-Induced Atrial Flutter: An Unusual Cause of Atrial Flutter - Kunnumpurath, Anthony (J Investig Med High Impact Case Rep, 2020)
Tick-borne illness has been increasingly on the rise, since the first human case was reported in the late 1980s. Ehrlichia chaffeensis is one of the most common reported causes of tick-borne illness, particularly in the southern states of the United States. The clinical picture presents as a paradigm to the clinician, often missing the diagnosis without an appropriate history being taken and sometimes mistreated for other conditions. With the number of cases on the rise, new manifestations and clinical presentations due to E chaffeensis continue to be reported. Our case report is one such case in a 46-year-old male from Arkansas, with known exposure to multiple tick bites who presented with classical symptoms and laboratory values of tick-borne illness leading to atrial flutter. This unusual manifestation of atrial flutter due to tick-borne illness is rare and poorly understood. Further studies on tick-borne illness due to E chaffeensis may be needed to understand the systemic causes of the bacteria. In addition, in our case report, we bring to attention the standard presentation (symptoms, signs, and laboratory values) of tick-borne illness due to E chaffeensis along with the current standard for diagnosis and treatment.